The Health Literacy Environment of a Regional Australian Elective Surgery Access Unit: consumer perspectives from pre-admission to post-discharge - Sarah Neil; Kylie Murphy; Glenda Chapman (ACHSM, 2019)
Background: Healthcare services should conscientiously ensure their health literacy environment (HLE) supports wayfinding, and provides comprehensible health information. Despite the increasing focus on the importance of evaluating and enhancing the HLE, consumer perspectives about HLE barriers and enablers have received limited attention in the published literature.  Objective: This study aimed to identify barriers and enablers in the HLE of the Elective Surgery Access Unit (ESAU) at Albury Wodonga Health in regional south-east Australia.  Methods:Three consumers participated in the study. Two of these participants completed a wayfinding interview, verbalizing the barriers and enablers encountered during wayfinding from the nearest carpark to the ESAU. All participants reviewed samples of written materials for ESAU consumers. Two participants, who had been discharged, commented on whether any important information was overlooked, from a post-discharge perspective. The data was categorized into inter-related themes within broader overarching domains.  Results:The helpfulness of the physical environment was one domain, involving three themes: signage, parking, and visual cues. The helpfulness of written information was another domain, involving three themes: comprehensiveness, readability and relevance. A third overlapping domain was: the importance of verbal information-giving. This domain also involved three themes: the importance of a phone number to seek assistance, a clearly identifiable reception area, and in-person communication.  Conclusions: The insights of these three service users can inform health services trying to enhance access for everyone needing healthcare. If more Australian health services reviewed their HLE, the findings could inform organizational improvements towards safer, more efficient, and higher quality healthcare.